Cardiorenal Syndrome: New Developments in the Understanding and Pharmacologic Management - House, Andrew A. (American Society of Nephrology, 2013)
Cardiorenal syndromes (CRSs) with bidirectional heart-kidney signaling are increasingly being recognized for their association with increased morbidity and mortality. In acute CRS, recognition of the importance of worsening kidney function complicating management of acute decompensated heart failure has led to the examination of this specific outcome in the context of acute heart failure clinical trials. In particular, the role of fluid overload and venous congestion has focused interest in the most effective use of diuretic therapy to relieve symptoms of heart failure while at the same time preserving kidney function. Additionally, many novel vasoactive therapies have been studied in recent years with the hopes of augmenting cardiac function, improving symptoms and patient outcomes, while maintaining or improving kidney function. Similarly, recent advances in our understanding of the pathophysiology of chronic CRS have led to reanalysis of kidney outcomes in pivotal trials in chronic congestive heart failure, and newer trials are including changes in kidney function as well as kidney injury biomarkers as prospectively monitored and adjudicated outcomes. This paper provides an overview of some new developments in the pharmacologic management of acute and chronic CRS, examines several reports that illustrate a key management principle for each subtype, and discusses opportunities for future research.